Restructurisation of the Polish defence industry - Jaworski, Jakub (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2006)
The article consists of three main parts. The first contains a short history and a description of the situation and potential of the Polish defence industry in years 1945-1990, and describes intensive development under USSR supervision, growing of employment, and dependency between the socialist countries’ defence industries. Signals of approaching troubles started to appear already at the end of 1980s. The main signs of incoming troubles were: overgrowth of employment, not introducing any significant new technologies, and the end of the times when the sales for almost 100% of the “S” (special) production were secured.The second part is a list of attempts at some reforms of the state-owned defence industry. The article lists trials of introducing the following restructurisation plans: - a sector study and general assumptions for the first stage of defence industry restructurisation - Proxy Ltd., 1991 - a draft of reconstruction of the defence industry - Ministry of Industry and Trade, 1991/1992 - a programme of consolidation and clearing of the defence industry companies of the debts - Ministry of Industry and Trade, 1993 - a programme of restructurisation of the defence industry and support for technical modernisation of the Armed Forces - Council of Ministers, 1999 - a strategy of the defence industry potential structural restructurisation in years 2002-2005 - Council of Ministers, 2002. This section of the article presents programmes description, goals, sources of financing, stages of realisation and the reasons why these programmes weren’t introduced. The majority of the information in this part of the article bases on the Supreme Chamber of Control report on restructurisation of the Polish defence industry.The third part contains conclusions and the discussion of what, according to the author, was a success, a failure and, most of all, what should be done in the future to make the state-owned (and not only) part of the Polish defence industry more modern and competitive on the world defence market.